Family Business Succession: Hofstede’s Value Dimension Among Chinese in the East Coast of Malaysia - Iskandar Hasan Tan Abdullah; Nur Azuki Yusuff; Aileen Farida Adam (2013)
Family business inheritance among the Chinese community is a tradition that is known by the business community worldwide. Thus, family business among the Chinese community in Malaysia is no stranger. In fact, the inheritance of this business provides a unique and exciting dimension to be investigated by the Malaysian business community. The paper explores the empirical evaluation of the influence of the family business inheritance among the Chinese, who managed to overcome obstacles and conflicts through discussion and negotiation. This paper uses correlation test to investigate the effect of inheritance in a family business among the Chinese, by the variables such as power distance, uncertainty avoidance, masculinity vs femininity, individualism vs collectivism, time orientation and impact on value dimension. In addition, this paper uses factor analysis and regression testing to determine the main cause of problems in the family business inheritance among the Chinese community. Primary data were collected between August and October 2011 using a questionnaire. Meanwhile, secondary data were gathered through library research and interviews with Chinese traders on the East Coast of Malaysia. Ironically, the young Chinese showed no interest in family business inheritance. In addition, the study also found that the older generation did not object to the will of young people who are their children. In addition, qualitative studies have found that the main reasons for refusal to inherit the family business among the younger Chinese generation is due to jobs that offer lucrative wages compared to profits earned through the family business. Several other factors are job status, education level and age factors that play a role in influencing the younger Chinese generation to not inherit the family business.